2023
DOI: 10.3390/plants12122283
|View full text |Cite
|
Sign up to set email alerts
|

Magnolin Inhibits Paclitaxel-Induced Cold Allodynia and ERK1/2 Activation in Mice

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a common side effect of anti-cancer drugs. The main symptoms often include sensory disturbances and neuropathic pain, and currently there is no effective treatment for this condition. This study aimed to investigate the suppressive effects of magnolin, an extracellular signal-regulated kinase (ERK) inhibitor substance derived from a 95% EtOH extract of the seeds of Magnolia denudata, on the symptoms of CIPN. A taxol-based anti-cancer drug paclitaxel (PTX) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, after repeated doses twice daily for 4 days, a significant analgesic effect was observed ( Figure 6C ). The results observed following the initial injection of magnolin suggest a discrepancy in its analgesic effectiveness between evoked and spontaneous pain (Cao et al, 2012 ; Kim N. et al, 2023 ). These results lead us to suggest that it would be more appropriate to test repeated dosing of magnolin in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, after repeated doses twice daily for 4 days, a significant analgesic effect was observed ( Figure 6C ). The results observed following the initial injection of magnolin suggest a discrepancy in its analgesic effectiveness between evoked and spontaneous pain (Cao et al, 2012 ; Kim N. et al, 2023 ). These results lead us to suggest that it would be more appropriate to test repeated dosing of magnolin in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the antioxidant activity, honokiol (HNK) displayed anti-inflammatory action in primary cultures of microglia and astrocytes stimulated by LPS, as demonstrated by the inhibition of expression of pro-inflammatory mediators, such as IL-6, IL-1β, iNOS, and TNF-α [ 22 ] and showed antinociceptive activity in inflammatory pain models [ 23 ]. Furthermore, a recent study showed the efficacy of magnolin, a neolignan obtained from the flower buds of Magnolia denudata , in attenuating paclitaxel-induced cold allodynia [ 24 ], In the effort to identify new potential therapies for NP, the purpose of our research was to evaluate the analgesic activity of an HNK-rich standardized extract of Magnolia officinalis Rehder & E. Wilson bark (MOE) in an animal model of neuropathic pain. The underlying molecular mechanisms of MOE and HNK were investigated in vitro.…”
Section: Introductionmentioning
confidence: 99%